Effect of Y2O3 content on microstructure and mechanical properties of ODS Ti–6Al–4V alloys fabricated by in situ atomization and SPS - Hyeon-Tae Im; Ryun-Ho Kwak; Sung-Min Park; Chang-Soo Park; Hyung-Ki Park (Journal of Materials Research and Technology)
In this study, the microstructure and mechanical properties of oxide dispersion strengthened (ODS) Ti–6Al–4V (Ti64) alloys fabricated via in situ gas atomization and spark plasma sintering (SPS) were investigated. Rod-shaped ingots of ODS Ti64 alloys containing 0.5, 1.0, and 2.0 wt% Y2O3 were prepared using vacuum arc remelting, and powders were subsequently fabricated via electrode induction melting gas atomization. The ODS Ti64 powders exhibited a spherical morphology, with fine Y2O3 particles smaller than 40 nm uniformly distributed within the powders. These powders were then consolidated by SPS, during which the addition of Y2O3 led to an increased in the sintering onset temperature. Although some coarsening of Y2O3 particles occurred during sintering, they remained smaller than 80 nm and were homogeneously dispersed in the sintered compacts, effectively suppressing grain growth and reducing grain size. Mechanical property evaluations revealed that both hardness and compressive strength improved as the Y2O3 content increased. Compression tests showed that the ODS Ti64 alloy containing 1 wt% Y2O3 exhibited significantly enhanced strength while maintaining a fracture strain comparable to that of the Ti64 alloy. In contrast, the ODS Ti64 alloy with 2 wt% Y2O3 showed reduced ductility. Overall, this study confirms the successful fabrication of ODS Ti64 alloys with finely dispersed Y2O3 particles via in situ gas atomization and SPS. Notably, the addition of 1 wt% Y2O3 provided the optimal balance of strength, hardness, and ductility.